1992
DOI: 10.1111/j.1365-2125.1992.tb04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of pseudoracemic nitrendipine to elucidate the metabolic steps responsible for stereoselective disposition of nitrendipine enantiomers.

Abstract: 1 The pharmacokinetics, protein binding, bioavailability and metabolism of (+)-R-and (-)-S-nitrendipine were studied in six healthy subjects following random oral administration of 20 mg (+)-R-, 20 mg (-)-S-and 20 mg R,S-nitrendipine (pseudoracemic mixture of 10 mg [13C4)-(+)-R-and 10 mg (-)-S-enantiomer). 2 After administration of the enantiomers pronounced differences in AUC (R: 29.9 + 20.1; S: 123.8 ± 63.7 ng ml-' h; P < 0.05), bioavailability (R: 10.7 ± 7.4%; S: 44.6 + 23.1%; P < 0.05) and Cmax (R: 14.4 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Nitrendipine is another dihydropyridine calcium channel blocker that follows a pattern of metabolism similar to nimodipine and nisodilpine. They all follow the oxidation of the dihydropyridine structure, hydroxylation to the methyl group and derivation of the corresponding carboxylic acids by the cleavage of the ester bonds [ 76 ].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Nitrendipine is another dihydropyridine calcium channel blocker that follows a pattern of metabolism similar to nimodipine and nisodilpine. They all follow the oxidation of the dihydropyridine structure, hydroxylation to the methyl group and derivation of the corresponding carboxylic acids by the cleavage of the ester bonds [ 76 ].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Previous studies have shown that the S‐enantiomer of nitrendipine is 7–8 times more potent than the R‐enantiomer [9]. In addition, the bioavailability of the S‐enantiomer is greater than that of the R‐enantiomer [10, 11]. Therefore, the measurement of plasma concentrations of these enantiomers separately may be relevant to our understanding of the clinical importance of the present drug interaction.…”
Section: Discussionmentioning
confidence: 99%